Motif Tenun Sebagai Bentuk Bahasa Rupa Dari Masyarakat Suku Mbojo di Bima Nusa Tenggara Barat - Erri Fajarriny Suwandi; Yan yan Sunarya (JURNAL RUPA, 2021)
One of the characteristics of Bima City lies in its handicrafts, namely woven fabrics made by the Mbojo Tribe for generations. The motifs that are often used are motifs with images of flowers, leaves, or lines. Each motif has its meaning and is a form of message used by the people of the Bima kingdom before they knew writing. Over time, the meaning of inherited motifs has shifted. The shift is marked by modern weavers who do not know the meaning. With this phenomenon, the knowledge passed down by previous generations will stop at the current weaver's so that the cultural values ??contained are non-existent and even difficult to translate. The primary study analyzes the Bima weaving motif by exploring the four main motifs to find their meaning. The research was conducted using a qualitative method. In this method, data collection was supported by a literature study, then field observations and interviews to determine the overall motive to comply with applicable regulations. The qualitative approach is followed by a more profound analysis using the theory of visual language forms. The purpose of this study is to provide a reference to the weavers of the Mbojo Tribe to find out the meaning of the motifs contained in the Bima weaving to preserve the Bima culture.